MULTIPLE BOTTOM-SIMULATING REFLECTIONS IN THE BLACK SEA: POTENTIAL PROXIES OF PAST CLIMATE CONDITIONS - Popescu I.; De Batist M.; Poort J.; Versteeg W.; Panin N.; Lericolais G.; Nouzé H.; Gillet H. (My University, 2006)
A previously unknown pattern of multiple bottom-simulating reflections (BSRs) occurs on high-resolution reflection seismic data in the Danube deep-sea fan, associated with acoustic features indicating free gas. Our study provides evidence that this pattern is developed in relation with the architecture of distinct channel-levee systems of the Danube fan. Channel-levee systems hosting multiple BSRs act as relatively sealed gas-bearing systems whose top is situated above the base of the gas hydrate stability zone (BGHSZ). Inside these systems, free gas accumulates below the BGHSZ under a combined lithological, structural and stratigraphical control. The uppermost BSR marks the current equilibrium BGHSZ, for a gas composition of more than 99% methane. Model-derived depths of the BGHSZ for different gas compositions and pressure-temperature conditions show that multiple BSRs would correspond to the BGHSZ either for (1) layers of gas hydrates with high contents of heavy hydrocarbons or hydrogen sulphide, or (2) stable climatic episodes with temperatures between glacial values and the present-day conditions. As the gas hydrate compositions required by hypothesis (1) are in sharp contradiction with the general background of the gas composition in the study area, we suggest that multiple BSRs are most probably relics of former positions of the BGHSZ, corresponding to successive steps of climate warming. In this case, they can provide sea-bottom paleotemperature values for these episodes, and hence they are potential new proxies for deciphering past climate conditions. © 2006 Elsevier B.V. All rights reserved.
Keywords: BLACK SEA; BOTTOM-SIMULATING REFLECTIONS; DEEP-SEA FAN; GAS; GAS HYDRATES; SEISMIC DATA